Adverse clinical outcomes among youths with nonsuicidal self‐injury and suicide attempts: a longitudinal cohort study. (2nd December 2021) - Bjureberg, Johan; Kuja‐Halkola, Ralf; Ohlis, Anna; Lichtenstein, Paul; D'Onofrio, Brian M.; Hellner, Clara; Cederlöf, Martin
Abstract : Background: More knowledge about risks of clinical outcomes associated with nonsuicidal self‐injury (NSSI) and suicide attempts (SAs) is needed to inform risk assessment and intervention. Methods: Longitudinal cohort study based on 1, 855 youths was clinically assessed for NSSI and SA, and followed up (from December, 2011 to December 2013) for the outcomes; diagnosed self‐injury, alcohol/substance use disorder, and psychiatric inpatient care data derived from Swedish registers. Hazard ratios (HRs) and 95% confidence intervals (CIs) of the outcomes were estimated with Cox regressions, and additionally adjusted for the potential effect of sex and the number of clinical assessments. NSSI and SA were treated as time‐varying covariates. Results: Youths with NSSI had elevated risks of all outcomes, compared with youths without NSSI or SA; the HR was 2.3, 95% confidence interval [1.6, 3.4] for self‐injury, 1.4 [0.9, 2.1] for alcohol/substance use disorder, and 1.3 [1.0, 1.7] for psychiatric inpatient care. Youths with SA displayed higher risks for the outcomes than the NSSI group; the HR was 5.5 [2.4, 12.6] for self‐injury, 2.0 [0.9, 4.4] for alcohol/substance use disorder, and 2.6 [1.5, 4.5] for psychiatric inpatient care. Youths with both NSSI and SA showed similar risks as youths with SA; HR 4.1 [2.0, 8.3] for self‐injury, 2.0 [1.1, 4.1] for alcohol/substance use disorder, but a higher risk of psychiatric inpatient care; HR 5.0 [3.1, 7.9]. All results remained virtually unchanged in the adjusted analyses. Conclusions: Youths with NSSI and/or SA had higher risks for subsequent adverse clinical outcomes. These excess risks were more pronounced among youths with SA and youths with both NSSI and SA, and the risk for psychiatric inpatient care was particularly high in youths with both NSSI and SA. Our findings suggest that early interventions for youths with NSSI or SA should not exclusively focus on suicide prevention, but also consider the risk of subsequent alcohol/substance use disorder.